Language of war in the Virtual Reality - Jolanta Szarlej; Aleksander Sapiński (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2023)
In the rapidly evolving Virtual World landscape, thelanguage of war crosses traditional boundaries, manifesting itself in unprecedented ways that demand linguistic analysis. This article delves into the multifaceted aspects of "The Language of War in the Virtual World," exploring linguistic theories, models and practical manifestations of the virtual domain. Using established linguistic frameworks, this exploratory work breaks down the constituent nuances of war-related discourse, shedding light on the distinctive linguistic features that characterize virtual conflicts. Through a comparative analysis of Polish and English languages, this study aims to uncover the subtleties of virtual war discourse, highlighting its profound impact on communication in this technologically mediatized environment.